Power Asymmetry and Learning in Teams: The Moderating Role of Performance Feedback - Van der Vegt, Gerben S.; de Jong, Simon B.; Bunderson, J. Stuart; Molleman, Eric (Organization Science, 2010)
Past research suggests that power asymmetry within teams can have a stifling effect on team learning and performance. We argue here that this effect is contingent on whether power advantages within a team are used to advance individual or collective interests. This study considers the moderating role of one factor that can influence the individual or collective orientation of team members—the type of performance feedback that a team receives. We propose that whereas individual feedback reinforces the negative effects of power asymmetry on team learning, group feedback fosters a collective orientation within a team that transforms power differences into a stimulus for team learning. Analysis of multisource, multimethod data obtained from 218 individuals in 46 teams provided support for these hypotheses. Results also suggested that team learning mediated the relationship between power asymmetry and team performance. These findings suggest that power asymmetry can be a resource for and not just an obstacle to team learning in power-asymmetric teams.